Effects of using lactic acid bacteria in the storage and subsequent anaerobic co-digestion of crushed kitchen garbage. (February 2021) - Tamaki, Shogo; Hidaka, Taira; Nishimura, Fumitake
Abstract: Anaerobic co-digestion of wastewater sludge and other types of organic waste with high moisture content is a promising approach for energy recovery. A novel organic waste collection system that stores disposer-crushed kitchen garbage with lactic acid fermentation in personal wastewater treatment systems, such as Johkasou, is proposed for centralized anaerobic co-digestion. In storage experiments, lactic acid fermentation of artificial kitchen garbage, which was seeded with lactic acid bacteria at the beginning of storage, lowered the pH to 3, and suppressed the solubilization of suspended solids (SS). The addition of household wastewater sludge did not affect these processes. The SS preservation ratio and the biogas production potential ratio in the subsequent anaerobic digestion were approximately 0.8. These results indicate that the storage of crushed kitchen garbage by lactic acid fermentation is an accessible and effective option for the collection and anaerobic co-digestion of kitchen garbage from Johkasou. Graphical abstract: Unlabelled Image Highlights: Storage of kitchen waste by lactic acid fermentation for anaerobic co-digestion. Lactic acid fermentation lowered pH to 3 and suppressed solubilization of garbage. Addition of household wastewater sludge did not affect this process. Preservation of biogas production potential ratio was approximately 0.8. Most detected bacteria were closely related to Lactobacillus.